This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: ( 1 2 x + 3 Â· 2) 42. Use lnâ€™s properties ln( x 2 Â· âˆš 3 x2) = ln( x 2 ) + ln( âˆš 3 x2) , ln( x 2 ) = 2ln( x ) and ln( âˆš 3 x2) = ln((3 x2) 1 2 ) = 1 2 ln(3 x2) . Rewrite the function: y = ln( x 2 âˆš 3 x2) = ln( x 2 ) + ln( âˆš 3 x2) = 2ln( x ) + 1 2 ln(3 x2) Date : 02/07/2000. 1 2 MATH 132 WI01 and so y = 2 1 x + 1 2 1 3 x2 Â· 3...
View
Full Document
 Spring '08
 Staff
 Calculus, Chain Rule, Derivative, Product Rule

Click to edit the document details